Perceptions of priority issues in the conservation of biodiversity and ecosystems in India. (July 2015) - Varma, Varun; Ratnam, Jayashree; Viswanathan, Vinatha; Osuri, Anand M.; Biesmeijer, Jacobus C.; Madhusudan, M.D.; Sankaran, Mahesh; Krishnadas, Meghna; Barua, Deepak; Budruk, Megha; Isvaran, Kavita; Jayapal, Rajah; et al.
Abstract: We report on the results of a country-wide survey of people's perceptions of issues relating to the conservation of biodiversity and ecosystems in India. Our survey, mainly conducted online, yielded 572 respondents, mostly among educated, urban and sub-urban citizens interested in ecological and environmental issues. 3160 "raw" questions generated by the survey were iteratively processed by a group of ecologists, environmental and conservation scientists to produce the primary result of this study: a summarized list of 152 priority questions for the conservation of India's biodiversity and ecosystems, which range across 17 broad thematic classes. Of these, three thematic classes—"Policy and Governance", "Biodiversity and Endangered Species" and "Protection and Conservation"—accounted for the largest number of questions. A comparative analysis of the results of this study with those from similar studies in other regions brought out interesting regional differences in the thematic classes of questions that were emphasized and suggest that local context plays a large role in determining emergent themes. We believe that the ready list of priority issues generated by this study can be a useful guiding framework for conservation practitioners, researchers, citizens, policy makers and funders to focus their resources and efforts in India's conservation research, action and funding landscape.